Leaf nutritional contents of the lychee tree in different phenological stages - Züge, Patrícia [UNESP]; Leonel, Sarita [UNESP]; Putti, Fernando Ferrari [UNESP]; Martins, Rafaelly Calsavara [UNESP] (Taylor & Francis, 2024)
The lychee tree (Litchi chinensis Sonn.) still needs adequate nutritional management and fertilization recommendations in Brazil. An adequate supply of nutrients for the lychee tree is the main requirement contributing to higher-quality fruit production. This work aimed to evaluate nutrient leaf contents in the phenological stages of the “Bengal” lychee tree. The experiment was conducted with the “Bengal” cultivar in the period corresponding to the years 2019–2022 at the São Manuel Experimental Farm of the Faculty of Agricultural Sciences (FCA), Universidade Estadual Paulista “Júlio de Mesquita Filho” (UNESP). The investigation collected leaf samples the plant’s four phenological stages. It evaluated the contents of nitrogen, phosphorus, potassium, calcium, magnesium, sulfur, boron, copper, iron, manganese, and zinc. The design was completely randomized, conducted in split plots (4 × 3), stage × cycle, with 10 repetitions. The plots represented phenological stages: full flowering (FF), fruit maturity (FM), 40 days after harvest (PC), and vegetative phase (VP). The subplots represented the evaluation cycles: cycle 1 (2019/2020 harvest), cycle 2 (2020/2021 harvest), and cycle 3 (2021/2022 harvest). There were climatic differences between the three evaluation cycles (years); the most significant water deficit was in 2020. There was a difference in nutrient content between production cycles and lychee tree phenological stages. The average contents in the leaves, at the different sampling times, followed the macronutrient order N > K>Mg > Ca > P>S, and Mn > Fe > B>Zn > Cu for the micronutrients.
Keywords: Bengal cultivar; Litchi chinensis; macronutrients; micronutrients; Sonn